The Effect of Transformational Leadership and Knowledge Sharing on Teacher Performance at SMP WR Soepratman East Kalimantan - Payong, Maria Lou; Supanto, Fajar; Sugito, Pudjo (Proceedings of International Conference of Graduate School on Sustainability, 2022)
Teacher performance is closely related to what the teacher does in the classroom and can affect teaching and learning activities in the classroom. Teacher performance includes all activities related to his professional duties as a teacher. Good teacher performance can be influenced by a leader who can give a positive influence on his subordinates because, without good leadership, an organization or institution will be difficult to achieve its goals. If the teacher's performance is good then quality education will be realized. Teacher performance is also determined by knowledge sharing, knowledge sharing is the availability of individuals in the organization to share the knowledge they have or get with other members of the organization. This study aims to analyze the effect of transformational leadership and knowledge sharing simultaneously on teacher performance, analyze the effect of transformational leadership and knowledge sharing partially on teacher performance, and analyze between transformational leadership and knowledge sharing which has a dominant effect on teacher performance. The sample used in this study was 32 respondents, and the sampling technique used was the census. The analysis technique used is multiple regression analysis. The results of the analysis show that transformational leadership and knowledge sharing simultaneously affect teacher performance. Transformational leadership affects teacher performance. Knowledge sharing affects teacher performance. Keywords: transformational leadership, knowledge sharing, teacher performance.